Cellular distribution of some intermediate filaments in the rat mammary gland during pregnancy, lactation and involution - Bayram, B.; Sagsoz, H.; Topaloglu, U. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2024)
Intermediate filaments (IFs) play a major role in determining and maintaining cell shape and anchoring intracellular organelles in place, in the tissues and organs of several species, starting from the early stages of development. This study was aimed at the immunohistochemical investigation of the presence, cellular localization and temporal distribution of the intermediate filaments keratin 8 (CK8), keratin 18 (CK18), keratin 19 (CK19), vimentin, desmin and laminin, all of which contribute to the formation of the cytoskeleton in the rat mammary gland during pregnancy, lactation and involution. On days 7, 14 and 21 of pregnancy (pregnancy period), on day 7 post-delivery (lactation period) and on day 7 post-weaning (involution period), under ketamine hydrochloride (Ketalar-Pfizer) (90 mg/kg) anesthesia, two mammary glands were fully excised from the abdominal region. It was determined that CK8 showed moderate immunoreactions in the alveolar and ductal epithelia, connective tissue and vascular endothelium of the rat mammary gland throughout pregnancy. On the 7 th day of pregnancy, CK18 expression was absent in the alveolar and ductal epithelia, but was observed weakly in some connective tissue cells. Throughout pregnancy, lactation and involution, the alveolar and ductal epithelia of the rat mammary gland were determined to be negative for CK19. Desmin expression predominated in the mammary myoepithelium and vasculature throughout all three of the investigated periods. While vimentin was not expressed in any of the mammary tissue components during pregnancy and lactation, its moderate expression was observed in the alveolar and ductal epithelia during involution. The involution period was also characterized by the vimentin negativity of the myoepithelium, stroma, fat cells and blood vessels of the mammary gland. Throughout all three periods, laminin expression was strong in the alveolar and ductal epithelia, stromal and myoepithelial cells and blood vessels, and did not vary in strength between the investigated periods. These findings demonstrated that intermediate filaments showed cell- and tissue-specific expression patterns in the rat mammary gland under the effects of pregnancy, lactation and involution.
Keywords: cytokeratin; desmin; involution; mammary gland